Matrix of Spiritual Sentiments in Literature: Array - Balțatu, Ludmila (Journal of Danubian Studies and Research, 2021)
Promotion of the nation’s spiritual values stands continually in sight of the romanian writers. That is, Its Majesty the word, when used with talent, with the knowledge in lyric, epic and dramatic writings, it is able to contribute significantly not just to the elucidation, but also to the widespread of our national treasure. It is not accidentally that many literary works, created by the most representative writers of the nation are dedicated to the Danube – the witness of our glorious historical events, a river that mystifies by its beauty, by the great variety of living creatures in its waters, by the message it sends to the growing generation to save and protect the nature, to take action against those who cause damage to it.